Clastic Sediments in the Butler Cave – Sinking Creek System, Virginia, USA - Chess, Daniel L.; Chess, Catherine A.; Sasowsky, Ira D.; Schmidt, Victor A.; White, William B. (Acta Carsologica, 2010)
The Butler Cave - Sinking Creek System in Bath County, Virginia, consists of a master trunk passage along the axis of a syncline with a trellis arrangement of dip-oriented side caves. The western set of dip passages contain a sequence of massively and chaotically bedded sand and cobble sediments. Massive cobble fills also occur in the strike-oriented trunk passage. Cave passages on the eastern side of the syncline contain mostly sand and silt. The light fraction of the sediments consists predominantly of quartz and rock fragments. The sediments contain several percent heavy minerals composed of iron oxides, zircon, rutile, tourmaline and other minerals. Measurement of the visible and near infrared diffuse reflectance spectra shows at least three populations of sediments to be present: an iron-rich, clay-poor group; a clay-rich group; and a gypsiferous sediment. The iron minerals provided a paleomagnetic signal. Sediments from the trunk passage, deposited by recent underground drainage, contained a normal pole direction. Sediments from the dip passages were paleomagnetically reversed, showing the deposition dates from prior to 780,000 years. In one instance reversed polarity deposits overlie normal polarity, implying a minimum age of 990,000 years for the reversed sediments.